2012
DOI: 10.1080/02640414.2012.685087
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of human handedness: Decreased one-hand bias and inter-manual performance asymmetry in expert basketball players

Abstract: Athletes frequently have to adapt their skills to fast changes of play, often requiring the flexible execution of a particular movement skill with either hand. To assess the influence of sport-specific expertise and extensive sport training on human laterality, a video analysis of regular basketball games was performed for professional, semi-professional, and amateur players to investigate how non-dominant hand use and proficiency change with increasing expertise. Our results showed that the right-hand (i.e. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 28 publications
6
46
3
1
Order By: Relevance
“…These results suggest that hand selection would result from the interaction of performance asymmetries and task demands. In the sport context, sensorimotor performance of the nonpreferred limb may be improved for tasks specifi cally practiced (e.g., Stöckel & Weigelt, 2012 ), but not for those that are rather diff erent, such as those described in the Edinburgh Inventory. No direct transfer of learning is expected between the sport tasks and the Edinburgh Handedness Inventory tasks, due to their diff erent control requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that hand selection would result from the interaction of performance asymmetries and task demands. In the sport context, sensorimotor performance of the nonpreferred limb may be improved for tasks specifi cally practiced (e.g., Stöckel & Weigelt, 2012 ), but not for those that are rather diff erent, such as those described in the Edinburgh Inventory. No direct transfer of learning is expected between the sport tasks and the Edinburgh Handedness Inventory tasks, due to their diff erent control requirements.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of fi ndings of smaller performance asymmetry in specifi c sport-related tasks ( Stöckel & Weigelt, 2012 ) and generalization of manual preference to tasks diff erent from those practiced ( Mikheev, et al ., 2002 ;Teixeira & Okazaki, 2007 ;Teixeira, et al ., 2010 ), the following hypotheses were tested:…”
mentioning
confidence: 99%
“…However, it has been hypothesised that choice of handedness can be modulated by task constraints and that handedness can be adapted to specific situations. 9 It does not appear unreasonable to conclude that jockeys can develop the ability to use the whip in both hands, given that it has been previously shown that bilateral practice can reduce limb dominance in participants in soccer 10 and judo. 11 If jockeys learn to use the whip in both hands, and choose to vary the hand in which it is used, it is likely that the skill is of some value to them.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the value of two-footed ability manifests in a substantial salary premium enjoyed by the 'two-footed' players (Bryson, Frick, & Simmons, 2012). Similarly, the capability of handling the ball equally well on both sides of the body makes a difference in basketball as well; a video analysis of basketball games of professional, semiprofessional, and amateur players demonstrated that professional players use their non-dominant hand more often and more efficiently than amateur players (Stöckel & Weigelt, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of non-preferred side skills in many sports (e.g. Carey et al, 2001;Petro & Szabo, 2016;Stöckel & Weigelt, 2012), the efficacy of mirror visual feedback, and the availability of mirrored video self-modelling, the method has received little VOLUME 13 | ISSUE 3 | 2018 | 623 attention. We are aware of three published papers testing the method of which one is ours (Petro & Bárdos, 2014;Steel, Adams, Coulson, Canning, & Hawtin, 2013;Steel & Ellem, 2016).…”
Section: Introductionmentioning
confidence: 99%